2013
DOI: 10.1021/je400501z
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid, Vapor–Liquid, and Vapor–Liquid–Liquid Equilibrium Data for the Water–n-Butanol–Cyclohexane System at Atmospheric Pressure: Experimental Determination and Correlation

Abstract: The temperature and the composition of the vapor-liquid-liquid equilibrium (VLLE), and the vapor-liquid equilibrium (VLE) of a ternary mixture of water -n-butanol -cyclohexane were measured at atmospheric pressure (101.32 kPa) in a modified dynamic recirculating still. As found in the literature, the experimental data obtained reveal a ternary azeotrope at 341.86 K with a mole-fraction composition of 0.281, 0.034 and 0.685 water, n-butanol and cyclohexane, respectively. The liquid-liquid equilibrium (LLE) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…[13] [9] azeotropów rozpatrywanych mieszanin trójskładnikowych i ich binarnych podukładów. Niezbędne obliczenia zostały wykonane symulatorem ChemCAD.…”
Section: Model Termodynamicznyunclassified
See 1 more Smart Citation
“…[13] [9] azeotropów rozpatrywanych mieszanin trójskładnikowych i ich binarnych podukładów. Niezbędne obliczenia zostały wykonane symulatorem ChemCAD.…”
Section: Model Termodynamicznyunclassified
“…Wybór tych substancji jest podyktowany dostępnością literaturowych danych eksperymentalnych VLLE [8][9][10][11] opracowanych przez ich autorów z myślą o osuszaniu n-butanolu. Dla trzech pierwszych układów dopasowano współczynniki równania NRTL, a w przypadku mieszaniny z n-heksanem wzięto je z pracy poprzedniej [20].…”
unclassified
“…These problems can be related to inconsistencies in the experimental data, but they can also result from the fact that the model cannot describe the reality perfectly. A well-known example is that the simultaneous description of vapor-liquid equilibria (VLE) and liquid-liquid equilibria (LLE) with G E -models often yields only poor results [3][4][5][6][7]. Also difficulties in describing both excess enthalpy and phase equilibrium data have been reported [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies using this method to extract alcohols such as ethanol, methanol, , and isobutanol with excellent performance. In order to expand the development of 1-butanol extraction units, many basic measurements about water + 1-butanol + solvents have been done on the ternary liquid–liquid equilibrium system, and relevant extractants show good extraction efficiency. It was found that light alcohol can be extracted from the aqueous solution using a heavy alcohol . As an extension, considering that the liquid–liquid equilibrium (LLE) data of {water + 1-butanol + 1-hexanol} and {water + 1-butanol + 1-octanol} ternary systems were not given in the literature, the performances of 1-hexanol and 1-octanol to separate water and 1-butanol were investigated systematically.…”
Section: Introductionmentioning
confidence: 99%